Optimalisasi Pemanfaatan Onggok Melalui Pengolahan Biologis Terhadap Parameter Rumen dan Kecernaan Zat-Zat Makanan Sapi - Yusuf Widodo; Arief Qisthon; Liman Liman (Politeknik Negeri Lampung., 2011)
The aims of the research were to study utilization of cassava waste through biological processing on rumen parameters and nutrient digestibility. The treatments was based on first years research. The treatment was used latin squere design 4x4.. Young cattle was used as material of this research. The treatments were arranged: R0: basal rations + 30% cassava waste (no treatment); R1 basal rations + 30% fermented cassava waste ( fermented by Aspergillus oryzae and prekursor urea 3 %); R2 : basal rations +30% fermented cassava waste ( fermented by Aspergillus oryzae and prekursor ammonium sulfat 1 %); R3 : basal rations + 15% fermented cassava waste ( fermented by Aspergillus oryzae and prekursor urea 3 %) + 15% fermented cassava waste ( fermented by Aspergillus oryzae and prekursor ammonium sulfat 1 %). The result showed that the treatments had no effect on rumen parameters and nutrient digestibility (dry matters and organic matters) Keywords: cassava waste, rumen parameter